2010
DOI: 10.1002/pbc.22725
|View full text |Cite
|
Sign up to set email alerts
|

Parental adjustment to the completion of their child's cancer treatment

Abstract: Childhood cancer treatment completion is a significant milestone. However, coming off treatment may be a time of psychological vulnerability for parents. This review assesses published research (1979-2009) on the psychosocial impact of treatment completion on parents. Fifteen articles met all inclusion criteria and demonstrated that while they celebrate treatment completion, parents (particularly mothers) can experience significant distress, including fear of recurrence, fatigue, and loneliness. Distress appea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
205
1
10

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 162 publications
(233 citation statements)
references
References 49 publications
17
205
1
10
Order By: Relevance
“…The current study illustrates that shortly after end of treatment, the corresponding proportions are comparable as need for support from psychologists was reported by 43% of mothers and 35% of fathers and need for support from social workers by 73% of mothers and 66% of fathers. Previous reports have proposed that the time following a child's cancer treatment completion is a vulnerable period for parents [1,3], which is supported by the findings of this study.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The current study illustrates that shortly after end of treatment, the corresponding proportions are comparable as need for support from psychologists was reported by 43% of mothers and 35% of fathers and need for support from social workers by 73% of mothers and 66% of fathers. Previous reports have proposed that the time following a child's cancer treatment completion is a vulnerable period for parents [1,3], which is supported by the findings of this study.…”
Section: Discussionsupporting
confidence: 90%
“…It has been proposed that parental distress abates over time [1]. However, in a previous report from this project we showed that PTSS in parents of children diagnosed with cancer is stable from three months after end of treatment up to five years after end of treatment [2].…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations